Evolving Role for Pharmacotherapy in NAFLD/NASH - Attia, Suzanna L. (Clin Transl Sci, 2020)
Nonalcoholic fatty liver disease (NAFLD) is a highly prevalent, dynamic disease that occurs across the age spectrum and can lead to cirrhosis and hepatocellular carcinoma. There are currently no US Food and Drug Administration (FDA) approved treatments for NAFLD; however, this is a field of active research. This review summarizes emerging pharmacotherapies for the treatment of adult and pediatric NAFLD. Investigated pharmacotherapies predominantly target bile acid signaling, insulin resistance, and lipid handling within the liver. Three drugs have gone on to phase III trials for which results are available. Of those, obeticholic acid is the single agent that demonstrates promise according to the interim analyses of the REGENERATE trial. Obeticholic acid showed reduction of fibrosis in adults with nonalcoholic steatohepatitis (NASH) taking 25 mg daily for 18 months (n = 931, reduction in fibrosis in 25% vs. 12% placebo, P < 0.01). Ongoing phase III trials include REGENERATE and MAESTRO‐NASH, which investigates thyroid hormone receptor‐β agonist MGL‐3196. Outcomes of promising phase II trials in adults with NASH are also available and those have investigated agents, including the fibroblast growth factor (FGF)19 analogue NGM282, the GLP1 agonist liraglutide, the FGF21 analogue Pegbelfermin, the sodium glucose co‐transporter 2 inhibitor Empagliflozin, the ketohexokinase inhibitor PF‐06835919, the acetyl‐coenzyme A carboxylase inhibitor GS‐0976, and the chemokine receptor antagonist Cenicriviroc. Completed and ongoing clinical trials emphasize the need for a more nuanced understanding of the phenotypes of subgroups within NAFLD that may respond to an individualized approach to pharmacotherapy.